Penggunaan Bahan Organik dan Kombinasinya dalam Formulasi Biofungisida Berbahan Aktif Jamur Trichoderma pseudokoningii Rifai. untuk Menghambat Jamur Ganoderma boninense Pat. secara in vitro - Elfina, Yetti; Ali, Muhammad; Saputra, Rachmad (Jurnal Natur Indonesia, 2016)
Trichoderma pseudokoningii has been applied as a biocontrol agent against fungal plant pathogen, such as Ganoderma boninense, the cause of stem rot disease on palm oil plants. To be more effectively applicable in the field, some experiments have been employed to formulate T. pseudokoningii in a biofungicide formulation amended with organic matter as its main nutrient resource, zealot as a carrier agent and cocoyam powder as a mixture agent. A research has been conducted to study the effect of various organic matters and their combinations in a biofungicide formulation of T. pseudokoningii on growth inhibition to G. boninense in-vitro and to obtain the best organic matters and their combinations in enhancing the growth of T. pseudokoningii and yet inhibiting G. boninense. The research has been conducted in the Laboratory of Plant Pathology, Agriculture Faculty, University of Riau from May to August 2012, using a completely randomized design consisting of 15 treatments (bagasse, rice husk, shrimp shell, dregs, and their combinations) and 3 replications. The data were statistically analyzed using analysis of variance, followed by Duncan’s New Multiple Range Test (DNMRT). The results indicated that organic matters and their combinations in the biofungicide formulation significantly affected the antagonistic capacity of T. pseudokoningii in inhibiting the growth of G. boninense in vitro. Rice husk, bagases, bagasse+rice husks, and bagasse+dregs were the best organic matters in enhancing the growth of T. pseudokoningii and its capacity to inhibit G. boninense in-vitro. It can also be concluded that shrimp shell, bagasse+shrimp shell, rice husk+shrimp shell, shrimp shell+dregs and rice husk+shrimp shell+dregs totally inhibited the growth of T. pseudokoningii in the biofungicide formulation.